Heart Rate Monitoring Device for Arrhythmia Using Pulse Oximeter Sensor Based on Android - Agustine, Lanny; Muljono, Ivan; Angka, Peter Rhatodirdjo; Gunadhi, Albert; Lestariningsih, Diana; Weliamto, Widya Andyardja (2018 International Conference on Computer Engineering, Network and Intelligent Multimedia (CENIM), 2018)
A monitoring and alert system for a patient with arrhythmia potential, especially during rest time at night, can reduce the fatality effect of the heart problem. General pulse oximeter connected with the Internet of things (IoT) technology enable a family member to remotely monitor the patient. The more important is the system ability to give realtime alarm to alert them when the patient in critical condition.The system uses a pulse oximeter sensor, a WLAN router to connect the device to the Blynk server, and the data could be displayed on an Android application. The hardware worn by the patient is battery powered. The battery capacity also monitored. The lowest accuracy of heart rate reading compared with the measured output of a fingertip pulse oximeter is 96.9% (normal, bradycardia, and tachycardia). The speed of data communication for remote monitoring depends on internet connection quality.